A Study on Case Settlement Mechanisms: An Analysis of Desertion by TNI Members in the KODAM IV/Diponegoro Region - Edy, Slamet Sarwo; Mustafa, Mustafa; Soge, Albertus D; Heniarti, Dini Dewi (Fakultas Hukum Universitas Widya Mataram, 2025)
The crime of desertion committed by military members in the area of Military Area Command (Kodam) IV/Diponegoro is in first place among other crimes. This has occurred for the last three years, from 2021 to 2023. The crime of desertion hurts many people, especially the perpetrators, their families, the general public, and the state, which has spent a lot of money and effort to educate and train deserters. The method used in this research is the juridical-empirical method, and field research that examines the suitability between theory and practice in society. Factors causing military members to desert in the Kodam IV/Diponegoro area include not wanting to be a soldier anymore (low mentality and discipline), having debts, family problems, fraud and embezzlement, and problems with seniors or commanders. Prevention of desertion crimes is by applying strict laws, as well as conducting periodic and continuous unit development.